Development of a food multimix to address malnutrition amongst the elderly - Matiwane, N. B. (My University, 2008)
Introduction and purpose - The study was conducted in order to determine the nutritional status of the elderly attending a care centre in Sharpeville in order to develop a novel food item, to address malnutrition and to test and analyse the novel food item for acceptability (sensory analysis) and shelflife. Methodology - A randomly selected sample of 170 elderly, including males and females, aged sixty and above participated in the research. A cross-sectional survey included sociodemographic, health and twenty-four hour recall questionnaires as well as anthropometric and biochemical measurements. Trained fieldworkers assisted with data collection dietary intake and food measurements consumption data were captured and analysed with assistance of a qualified dietician using a Food Finder ® version 3.0 program in to determine the frequency, mean and standard deviations. The socio-demographic and health data, biochemical and anthropometric measurements were analysed for means and SDs. Results - Although 100 percent of the elderly received a monthly pension, the majority (72 percent) were bread winners in the households. The majority of households (65,8 percent) had a monthly income ofR 501-1 000. Eighty two percent of the respondents indicated that they bought food once a month and the food was bought mostly from local supermarkets (68,2percent) which are generally very expensive. Most households (63,1percent) spent less than R200 on food per week. Taking into consideration that the average household size was 4,9, it was calculated to be less than R5,80 per person per day. The Top 20 food consumption list indicated that the majority of food items consumed were carbohydrate-based. Dietary intake results confirmed that these households consumed mainly a carbohydrate-based diet and although the daily protein intake was sufficient, the diet was also deficient in total energy and dietary fibre, as well as a number of micronutrients including calcium, magnesium, zinc, selenium, iodine, thiamine, riboflavin, vitamins B6, C, D, E, biotin, pantothenate and folate. These findings indicated the prevalence of undernutrition The biochemical data showed that 73,1 percent of the elderly had low serum zinc levels. A large percentage of men and women had sub-optimal haemoglobin levels. Most of the biochemical variables were within the normal range, however the mean cholesterol level was 5,4 ± 1 ,4mmol/l which was higher than the normal range of 5,2mmolll. The majority ofthe females were overweight and obese, signifying overnutrition in the sample of elderly people. The health status of the respondents was also compromised. A large number of subjects were taking chronic medication (55,9percent) and suffered from a number of disorders including painful joints (70,6percent), enteral infections 72,4 percent) and chronic headaches (48,2percent). Forty one percent received chronic hypertension medication A food multimix was formulated, which involved the blending of locally available, affordable, culturally acceptable and commonly consumed food commodities mixed proportionally, drawing on the 'nutrient strengths' of each component of the mix in order to optimise the nutritive value of the end-product without the need for fortification. The initial estimates of energy and nutrient content of the ingredients needed the appropriate food databases. The nutrient content was calculated using the SA food composition data and Food Finder/Dietary Manager®. At least 30 percent target ratio of the RDA was met in most nutrients in the food multimix. Proximate analysis was carried out to determine macronutrients such as energy, protein, carbohydrate and micronutrients such as zinc and iron content of multimixes. Carbohydrate and energy content were derived using data gained from the analytical procedures. Sub-samples of formulated FMM recipes were taken and prepared for analysis and shelf life testing of the FMM, soup and spinach muffin was also carried. The end products of multimix formulated were two recipes namely cream spinach soup and low sodium spinach muffms. Eighty percent accepted the soup colour and 50percent liked the flavour, 55 percent of the elderly accepted the appearance, 75percent accepted the smell of the product. The dried spinach was mixed with the apple blended well and regarding taste, only 15 percent disliked the taste. Conclusions: The results of this study confirmed that a novel food item such as FMM can be developed to meet certain criteria. Recommendations: Further research is required where long-term effects of the implementation of the multimix in the diet of the elderly can be investigated.
M. Tech. (Department of Hospitality, Faculty of Human Sciences), Vaal University of Technology
Keywords: Elderly people nutrition; Food multi-mix; 641.35655; Older people -- Nutrition -- South Africa